Prospek Pengembangan Agroindustri Budidaya Tanaman Porang untuk Kesejahteraan Ekonomi Keluarga Petani Porang pada Kec. Kualuh Kab. Labuhan Batu Utara - Syafitri, Mita Nur; Nawawi, Zuhrinal M. (Lembaga Yasin AlSys, 2024)
Development in the agricultural sector will be more optimal if it is combined with the management of superior commodities. One commodity that has the potential to become a superior commodity is the porang plant. Prospects where a decision of possible opportunities and obstacles faced and strategies for prosperity. This research aims to find out Prospects for the Development of Porang Plant Cultivation Agro-Industry for the Economic Welfare of Porang Farmer Families. The problem studied in this research is what are the prospects for the development of the Porang plant cultivation agro-industry for the economic welfare of Porang farmer families, Kualuh Hulu District. North Labuhan Batu. This research uses a qualitative method, where data collection techniques use interviews, observation, documentation and use the R/C and B/C formulas to determine the feasibility of future prospects for cultivating porang plants. Based on the results of this research, it shows that there are several strategies in cultivating porang plants to achieve prosperity, namely external and internal factors.